Designing a Portable Camera Image Acquisition System Operating Within an Indoor Wi-Fi Network and Optimized for A Robotic Vehicle - Priya George, Anu; Felix Joseph, X (International Journal of Engineering and Technology, 2018)
Nowadays people working in industrial sectors face lot of problem like placing a valuable objects or things in some place unknowingly and searching it. To overcome this problem we are moving into the field of Object searching and identify which assist industrial sectors and research labs. Object searching mechanism is a challenging task. Real time object search poses many difficulties in recognizing objects. We are tending to do real time image capturing as well as recognizing techniques and it will forward data through Wi-Fi used in embedded device. The proposed system makes use of computer vision techniques based on real time image processing and recognizing the object and send via internet to PC.Â Â Â